2014
DOI: 10.1103/physrevd.89.064002
|View full text |Cite
|
Sign up to set email alerts
|

Wormhole solutions supported by interacting dark matter and dark energy

Abstract: We show that the presence of a nonminimal interaction between dark matter and dark energy may lead to a violation of the null energy condition and to the formation of a configuration with nontrivial topology (a wormhole). In this it is assumed that both dark matter and dark energy satisfy the null energy condition, a violation of which takes place only in the inner high-density regions of the configuration. This is achieved by assuming that, in a high-density environment, a nonminimal coupling function changes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Such anisotropic scenarios are obtained also for regular static, spherically symmetric solutions describing wormholes supported by dark matter non-minimally coupled to dark energy in the form of a quintessence scalar field [11].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Such anisotropic scenarios are obtained also for regular static, spherically symmetric solutions describing wormholes supported by dark matter non-minimally coupled to dark energy in the form of a quintessence scalar field [11].…”
Section: Introductionmentioning
confidence: 77%
“…The obtained negative values of the n-parameter are less than −1. This implies that there is no spherically symmetric traversable wormholes characterized by a radial metric component given by g −1 rr = 1−(r 0 /r) n+1 (with n > −1), and sustained by isotropic pressure sources with a linear equation of state (11), independently of the form of the redshift function φ(r). The implications of this result tell us that we must consider more general forms of the shape function b(r) and/or of the equation of state of the isotropic pressure p(ρ).…”
Section: On Spherical Wormholes With Isotropic Pressure and Lineamentioning
confidence: 99%
“…We can also extend the original model of wormhole to a more generalized cosmological traversable wormholes by introducing the fifth coordinate z as detailed in, 34 such that It is known that the presence of a nonminimal interaction between dark matter and dark energy may lead to a violation of the null energy condition and to the formation of a configuration with nontrivial topology like a wormhole. 35 Here the violation of N.E.C takes place only in the inner high-density regions of the configuration both between 2 < < 6 . .…”
Section: Final Remarksmentioning
confidence: 89%
“…To close this section let us explore the stability of the obtained solutions using equilibrium conditions. For this purpose we utilize the TOV equation which is given by the conservation equation equation (16). The equilibrium state of the wormhole structure is determined through the three terms in this equation which are defined as gravitational, hydrostatic and anisotropic forces, respectively…”
Section: Solutions With φ(R) ̸ =mentioning
confidence: 99%
“…Work along this line has been performed in the literature for different matter distributions, for example, traversable wormhole geometries constructed by matter fields with exotic EMT have been studied in [14]. The case of phantom or quintom-type energy as the ingredient to sustain traversable wormholes has been investigated in [15] and wormholes supported by nonminimal interaction between dark matter and dark energy has been explored in [16], see also [17] for a comprehensive review. At quantum level, it has been shown that some effects due to quantum field theory, e.g.…”
Section: Introductionmentioning
confidence: 99%